Experimental investigation of the effect of inrush current created by LED drivers on switching elements - AKAR, ONUR; TERZİ, ÜMİT KEMALETTİN (My University, 2024)
The demand for lighting technology is increasing rapidly with the increasing population and the advancement of industrialization. Significant developments are taking place in the field of lighting to meet this demand. LED lighting technology, which is the most current of these developments, is preferred to a high degree as it is more efficient, long-lasting, and advantages compared to conventional lighting technologies. However, this technology is still in its development stage and problems may be encountered that need to be solved. In this study, the problems that caused by inrush current and damage to the switch contacts of LED armatures using different protection classes as a result of multiple switching were observed with switching elements complying with IEC 60669-1 standards. The damage on these two switching elements was tested by connecting them with 69 LED armaturesof 12A-36W and starting-stopping 10000 times, 40 times per minute. As a result of the test, corrosion/damage that could cause major fires was observed in the LED switching elements and pictures were taken with the help of Scanning Electron Microscope (SEM).The study shows the importance of creating a special international material standard for LED switchingsystems and ensuring that manufacturers comply with this standard.Keywords:Lighting, LED, Inrush Current, SEM
Keywords: Lighting; LED; Inrush Current; SEM